How problem gambling by a male partner contributes to intimate partner violence against women: a gendered perspective. Issue 1 (2nd January 2022) - Hing, Nerilee; O'Mullan, Catherine; Breen, Helen; Nuske, Elaine; Mainey, Lydia
ABSTRACT: This paper adopts a gendered perspective exploring how gambling by a male partner contributes to intimate partner violence (IPV) against women. Unstructured interviews with 30 women with lived experience of male partner violence linked to his gambling were analyzed using adaptive grounded theory. Gendered drivers of violence set the context for IPV experienced by these women. Their male partners held strict patriarchal views about gender roles, controlled decision-making, restricted the woman's independence, and condoned using violence against women. Gambling by the male partner interacted with these gendered drivers to increase the frequency and severity of IPV. They prioritized their gambling above the family's welfare, controlled household finances, and coerced the woman into providing money. Gambling created situations that increased IPV, including anger over losses, family stressors and conflicts, with violent backlash silencing the woman's objections. Violence intensified as the gambling escalated, with short-term cycles of violence directly linked to gambling events. Women experienced financial, psychological, physical and sexual abuse, and patterns of coercive control that maintained a climate of fear. These findings reveal the centrality of gender inequality within intimate relationships as a foundation for IPV, which is then exacerbated by the perpetrator's gambling.